When the Utopia Became Reality: Luis Emilio Recabarren and the Chilean Reception of the Russian Revolution - Pinto-Vallejos, J (STATE ACAD UNIV HUMANITIES, 2018)
Luis Emilio Recabarren, founder of Chile s Communist Party and symbolic "hero" of the Chilean left, was an avowed and sustained admirer of the Bolshevik Revolution. In spite of that, and of some strains that may be detected in his postrevolutionary discourse, the practical politics he endorsed in Chile diverged considerably from the Leninist canon in at least three matters: the structure and operation of the party, the appeal to revolutionary violence, and the validity of acting within "bourgeois" institutions. This paper describes and analyzes such tensions, suggesting possible explanations and projecting them onto the overall history of the Chilean Left during the 20th Century.
Keywords: Russian Revolution; Communist Party of Chile; Luis Emilio Recabarren